2015
DOI: 10.1186/s13256-015-0534-7
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral uveitis and Usher syndrome: a case report

Abstract: IntroductionUsher syndrome is a genetically heterogeneous condition and represents the most common cause of inherited combined vision and hearing loss. Deficits manifest as sensorineural hearing loss that typically develops at a young age and retinitis pigmentosa that can lead to peripheral vision loss and night blindness. As a result, this syndrome can have a significant impact on a patient’s quality of life.Previous studies have described an association between Usher syndrome and Fuchs’ heterochromic iridocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
1
2
0
4
Order By: Relevance
“…In general, the majority of reports about RP association with uveitis focused on FHU. These reports are not so large like mentioned above [3,8,16,20,25,26,27]. None of our patients had signs of FHU and all cases were bilateral.…”
Section: Discussionsupporting
confidence: 57%
“…In general, the majority of reports about RP association with uveitis focused on FHU. These reports are not so large like mentioned above [3,8,16,20,25,26,27]. None of our patients had signs of FHU and all cases were bilateral.…”
Section: Discussionsupporting
confidence: 57%
“…It is initially manifested by symptoms of night blindness, followed by peripheral visual field constriction and by loss of central vision in the most advanced stages [ 10 ]. Several studies have also demonstrated that uveitis is not an uncommon condition in RP patients [ 11 , 12 , 13 , 14 ]. However, the underlying mechanism explaining why some patients with RP are prone to AU, and vice versa, is largely unknown and remains an important issue to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The patient was first diagnosed of pars planitis. Few publications of uveitis coexisting with RP have been reported, specially a form of non-granulomatous uveitis called Fuchs’ heterochromic iridocyclitis [ 11 – 14 ]. Dust-like particles in the vitreous are present in the great majority of young individuals with RP.…”
Section: Discussionmentioning
confidence: 99%